2007
DOI: 10.1111/j.1440-1843.2007.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial heat shock protein‐induced blood T lymphocytes subsets and cytokine pattern: Comparison of sarcoidosis with tuberculosis and healthy controls

Abstract: After Mtb-hsp stimulation, increased levels of pro-inflammatory cytokines, TNF-alpha and IL-6 were found in sera from SA and TB patients in comparison with healthy controls; SA patients demonstrated the lowest levels of IL-4 and the highest levels of IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 37 publications
1
66
1
7
Order By: Relevance
“…Two studies demonstrate the presence of circulating antibodies against mycobacterial cell culture extracts in subsets of patients with sarcoidosis [96,97]. More recently, Drake and colleagues demonstrated sarcoidosis patients have immune responses to mycobacteria-derived antigens to ESAT-6, CFP-10, antigen-85A, and superoxide dismutase while Dubaniewicz and colleagues report immune responses to mycobacterial heat shock proteins in sarcoidosis [98][99][100][101][102][103][104]. There may be a genetic basis for responses to mycobacterial antigens in sarcoidosis (Table 2).…”
Section: Role Of Mycobacterial Organisms In Sarcoidosismentioning
confidence: 96%
“…Two studies demonstrate the presence of circulating antibodies against mycobacterial cell culture extracts in subsets of patients with sarcoidosis [96,97]. More recently, Drake and colleagues demonstrated sarcoidosis patients have immune responses to mycobacteria-derived antigens to ESAT-6, CFP-10, antigen-85A, and superoxide dismutase while Dubaniewicz and colleagues report immune responses to mycobacterial heat shock proteins in sarcoidosis [98][99][100][101][102][103][104]. There may be a genetic basis for responses to mycobacterial antigens in sarcoidosis (Table 2).…”
Section: Role Of Mycobacterial Organisms In Sarcoidosismentioning
confidence: 96%
“…If the remaining parenchymal cells cannot re-establish the normal architecture, T H 2 type cytokines (e.g. IL-4, IL-5, IL-10, IL-13) and macrophage-derived factors including fibronectin, platelet-derived growth factor, insulin-like Immunological markers of sarcoidosis 57 (Saboor et al 1992;Grosser et al 1999;Li et al 1999;Klemen et al 2000;Drake et al 2002;Eishi et al 2002;Gazouli et al 2002;Gupta et al 2007), which could suggest cell-wall deficient mycobacterial infection (Kon and du Bois 1997;Brown et al 2003), however, others have not found PCR evidence of mycobacterial DNA or RNA (Lisby et al 1993;Cannone et al 1997;Vokurka et al 1997) Elevated circulating IgG directed against mycobacterial catalase-peroxidase (KatG) peptides in sarcoidosis patients and other circulating antibodies against mycobacterial antigens (Song et al 2005), and other evidence of BAL and peripheral blood mononuclear cell responses to Mycobacterium tuberculosis heat shock proteins, mycolyl transferase antigen 85A, superoxide dismutase A, ESAT-6 and KatG peptides Drake et al 2007;Dubaniewicz et al 2007;Hajizadeh et al 2007;Allen et al 2008;Oswald-Richter et al 2009;Dubaniewicz 2010). A large worldwide study confirmed T H 1 responses to Mycobacterium tuberculosis KatG despite differences in patient phenotype, genetic and prognostic characteristics and showed that mKatG reactive CD4?…”
Section: Immunopathogenesis Of Sarcoidosismentioning
confidence: 96%
“…An aliquot of PBMCs was analysed by flow cytometry (reviewed in [31,32]). The population of PBMCs, that is, lymphocytes and monocytes together, was chosen to mimic in vivo occurring conditions, including possible cell-tocell interactions of different PBMC subpopulations.…”
Section: Isolation Of Pbmcsmentioning
confidence: 99%